Pemetaan Puskesmas dan Tenaga Kesehatan di Kabupaten Kendal Menggunakan SIG Tahun 2024 - Najwa Mahdewi Syahita; Bambang Agus Herlambang; Ahmad Khoirul Anam (JOURNAL SAINS STUDENT RESEARCH, 2026)
The distribution of health facilities and personnel is crucial for ensuring equitable access and quality of public health services. The objective of this study is to analyze the distribution of community health centers (Puskesmas) and health personnel in Kendal Regency in 2024 using a Geographic Information System (GIS). The approach used in this study is spatial descriptive, utilizing secondary data that includes spatial data on the location of community health centers and sub-district boundaries, as well as non-spatial data on the number of health personnel. The data analysis process was carried out using QGIS software, through the steps of processing, integrating spatial and non-spatial data, and presenting information in thematic map and WebGIS formats. The findings of this study indicate that the distribution of community health centers and health personnel in Kendal Regency is not evenly distributed among sub-districts. Nurses and midwives tend to be more well-dispersed, while doctors, pharmacists, and nutritionists are still concentrated in certain areas. The use of GIS has proven effective in presenting spatial information in a clear and comprehensive manner, which serves as a basis for planning for equitable distribution of health services.